The effetiveness of various sequestrants on the reduction of cadmium and lead levels in Remis (Donax sp.) - In-In Hanidah; Jedi Riazi; Tita Rialita; Sumanti Debby Moody; Yuli Andriani; Noor Taufiq; Annisa Ratri Utami; Laras Aprilianti (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Mussels (Donax sp.) are marine shellfish that tend to be contaminated with heavy metals as they are filter feeders. Heavy metal levels can be reduced by immersion in sequestrants. This study aimed to measure the effectiveness of the optimal sequestrant to reduce heavy metal levels in mussels. This experimental study was conducted at the Food Technology Laboratory of Padjadjaran University in January-April 2024 using samples of mussels (Donax sp.) from Cirebon, Indonesia. The data processing method used was a Randomized Group Design with five treatments consisting of soaking mussels in distilled water, 25% citric acid, 25% tamarind, 25% tomato, and 25% Pidada; each repeated 3x. The results showed that the most optimal organic sequestrant in reducing heavy metals was Pidada fruit with the effectiveness of reducing cadmium metal 21,195%, lead metal 6,543%, total citric acid 0.552%, water content 76.953%, and antioxidant activity based on IC50 value of 19,537 ppm with a very strong category. In conclusion, the Pidada fruit is the most optimal organic sequestrant for reducing heavy metal levels in mussels (Donax sp.) and has very strong antioxidant activity, making it effective for reducing heavy metal contamination.